Pattern Of Kyai Parenting In Building Character At Daar El Qolam 2 Islamic Boarding School Tangerang And La Tansa Mashiro Lebak Islamic Boarding School - Solihin, Solihin; Supiana, Supiana; Arifin, Bambang Samsul; Jamaludin, Dindin (Pusat Publikasi Nusantara, 2022)
Both Daar El Qolam 2 and La Tansa Mashiro are Islamic Educational Institution that has a special characteristic. In the implementation of Kyai’s parenting, there are many things that determine the formation of the character of the santri. Therefore, The Institution efforted some ways to overcome an ideal of parenting style to develop students’s character. This research attempts investigation on; 1) Objective of Kyai’s parenting style, 2) Programme of Kyai’s parenting, 3) Implementation of Kyai’s parenting, 4) Evaluation of Kyai’s parenting, 5) Advantage and disadvantage of Kyai’s parenting, 6) The impact of Kyai’s parenting. The reseach design uses a theory of Educator or teacher, parenting style, and implementation of Kyai to build character. The research employes a descriptive qualitative method with data analysis. Collecting data through observation, interview and documentation study. The results of research showed; 1) the kyai's parenting style in the Daar el Qolam 2 Islamic boarding school and the La Tansa Mashiro Islamic boarding school is classified as good in terms of the system aspect, management well-structured, as well as the rules and regulations in the boarding school. In the policy aspect, the pattern of parenting is still dominant depending on the existence of kyai. 2) The kyai parenting program at Daarel Qolam 2 Islamic Boarding School and La Tansa Islamic Boarding School is to build characters who master Islamic religious knowledge, master Arabic and English, understand information technology, extracurricular activities, santri’s organization, study the ancient yellow book, study general material, learning to be a prayer priest. Learning public speaking in Indonesian, Arabic, and English. 3) Implementation of the character development program for students at the Daar el Qolam and La Tansa Mashiro Islamic boarding schools went well in the aspects of mastering Islamic religious knowledge, mastering Arabic and English, mastering technology and information, extracurricular programs, yellow book studies, speeches in Arabic, English, and Indonesian. 4) Evaluation of the kyai's parenting style at the Qolam 2 Islamic Boarding School and the La Tansa Mashiro Islamic Boarding School was very good. This has been proven by the form of reports every day, weekly, and monthly. 5) The advantage factor at Daar el Qolam 2 Islamic Boarding School and La Tansa Mashiro Islamic Boarding School are in human resources, plus the teachers in both Islamic boarding schools live in the same area or dormitory. The disadvantage factor from the human resource element is sometimes the teachers do not carry out the supervision or guidance process optimally. 6) The kyai’s parenting style of the Daarel Qolam Islamic boarding school has a positive impact on character building. Meanwhile, The kyai’s parenting style of La Tansa Mashiro Islamic boarding school has a positive impact on character building.